Low-dose computed tomography screening for lung cancer in populations highly exposed to tobacco: A systematic methodological appraisal of published randomised controlled trials. (July 2016) - Coureau, Gaëlle; Salmi, L. Rachid; Etard, Cécile; Sancho-Garnier, Hélène; Sauvaget, Catherine; Mathoulin-Pélissier, Simone
Abstract: Low-dose computed tomography (LDCT) screening recommendations for lung cancer are contradictory. The French National Authority for Health commissioned experts to carry a systematic review on the effectiveness, acceptability and safety of lung cancer screening with LDCT in subjects highly exposed to tobacco. We used MEDLINE and Embase databases (2003–2014) and identified 83 publications representing ten randomised control trials. Control arms and methodology varied considerably, precluding a full comparison and questioning reproducibility of the findings. From five trials reporting mortality results, only the National Lung Screening Trial found a significant decrease of disease-specific and all-cause mortality with LDCT screening compared to chest X-ray screening. None of the studies provided all information needed to document the risk-benefit balance. The lack of statistical power and the methodological heterogeneity of European trials question on the possibility of obtaining valid results separately or by pooling. We conclude, in regard to the lack of strong scientific evidence, that LDCT screening should not be recommended in subjects highly exposed to tobacco. Highlights: Screening recommendations for lung cancer are contradictory. Methodological issues were not properly considered in previous reviews. Risk-benefit ratio is insufficiently documented in subjects highly exposed to tobacco. Heterogeneity of European trials doubt on the possibility of pooling future results. Evidence in this context is too scarce to recommend lung cancer screening.